Kinetic modeling and occupancy measures of the norepinephrine transporters in baboons using single photon emission computed tomography with 123I‐INER. Issue 1 (31st October 2012) - Dos Santos Tavares, Adriana Alexandre; Barret, Olivier; Batis, Jeffery; Alagille, David; Koren, Andrei; Papin, Caroline; Kudej, Greg; Nice, Katie; Kordower, Jeffrey H.; Cosgrove, Kelly P.; Kloczynski, Tracy; Brenner, Eric; et al.
Abstract This study aims to investigate the pharmacokinetics of a recently developed radiotracer for imaging of the norepinephrine transporter (NET) in baboon brain, 123I‐INER, using single photon emission computed tomography (SPECT). In addition, it also aims to determine NET occupancy by atomoxetine and reboxetine, two selective norepinephrine reuptake inhibitors, using 123I‐INER in baboons. Baseline and preblocking studies with a high dose of atomoxetine (0.85 mg/kg) were conducted in three baboons using SPECT with 123I‐INER administered as a bolus. Kinetic modeling analysis was investigated for different models, namely invasive and reference tissue models. Bolus plus constant infusion experiments with displacement at equilibrium using six different doses of atomoxetine (0.03–0.85 mg/kg) and four different doses of reboxetine (0.5–3.0 mg/kg) were carried out in several baboons to obtain occupancy measurements as a function of dose for the two NET selective drugs. Results showed that reference tissue models can be used to estimate binding potential values and occupancy measures of 123I‐INER in different brain regions. In addition, the apparent volume of distribution was estimated by dividing concentration in tissue by the concentration in blood at 3 hours postinjection. After administration of atomoxetine or reboxetine, a dose‐dependent occupancy was observed in brain regions known to contain high densities of NET. In conclusion, pharmacokinetic properties of 123I‐INER were successfully described, and obtained results may be used to simplify future data acquisition and image processing. Dose‐dependent NET occupancy for two selective norepinephrine reuptake inhibitors was successfully measured in vivo in baboon brain using SPECT and 123I‐INER. Synapse, 2013. © 2012 Wiley Periodicals, Inc.